Ishmael Sunga, SACAU, on what a work programme on agriculture would mean to smallholder farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
During the 29 Brussels Briefing on 27 September 2012, Ishmael Sunga from the Farmer's Organisation Southern African Confederation of Agricultural Unions (SACAU), spoke about what they want from the ongoing climate change negotiations and what farmers in developing countries need in order to adapt successfully to climate change. In this video clip Mr. Sunga gives his views on the topic, as well as what the establishment of a work programme on agriculture within the UNFCCC climate negotiations would mean to smallholder farmers, exclusively to the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). SACAU is a valuable work partner to CCAFS. Read more about CCAFS: www.ccafs.cgiar.org Learn more about SACAU: www.sacau.org